2012
DOI: 10.3126/mjsbh.v10i1.6446
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Analysis of Ovarian Tumours at Birendra Military Hospital

Abstract: Introduction:Ovarian cancer is the second most common genital tract malignancy accounting for 25% gynaecological malignancy. This study was conducted to determine the incidence, epidemiological factors and clinical presentation of different types of ovarian tumours their correlation with histopathology. Methods: This is a descriptive study conducted in Birendra Military Hospital over a period of 2 years. The case records of all the patients with ovarian tumur was analyzed. Results: Of the total of 135 adnexal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…20 In a study done by Khatri et al, 68.0% of ovarian tumors were benign and 32.0% were malignant. 21 The difference is probably because our study was undertaken in a referral hospital and malignant tumors diagnosed before surgery were referred to this center.…”
Section: Resultsmentioning
confidence: 99%
“…20 In a study done by Khatri et al, 68.0% of ovarian tumors were benign and 32.0% were malignant. 21 The difference is probably because our study was undertaken in a referral hospital and malignant tumors diagnosed before surgery were referred to this center.…”
Section: Resultsmentioning
confidence: 99%
“…Table 5 shows the studies done in other institutions in Nepal where the incidence of malignant ovarian tumor ranges from 10-29%. [3][4][5][6] Study done by Mondal et al 7 showed that benign tumors constituted 63%, malignant 29.6% and borderline tumors 7.3%. Other studies by Gupta, 8 Malli, 9 Bukhari 10 and Iyoke 11 also showed slightly higher malignancy rates 22.9%, 27%, 20% and 25% respectively.…”
Section: Incidence Of Malignancy/borderline Tumorsmentioning
confidence: 99%
“…tumours in many regions are of epithelial origin, accounting for about 40-60%. [1,2] These tumours include serous, mucinous, endometroid, clear cell and Brenner subcategories.…”
Section: Annals Of Health Research Volume 6 Issue No 2 2020_____________________185mentioning
confidence: 99%